Issues of Improving the Use of Applied Decorative Arts - Payzullaeya Dilnozaxon Ismoiljonovna (Peerian Journals Publishing, 2022)
This article discusses in detail the formation and development of applied decorative arts, types of decorative arts, their elements, the issues of improving their use, and the prospects for the future.
Keywords: applied arts; decoration; carving; decorative-applied arts